(untitled) (International Journal of Economics Management and Social Science, 2026)
Background: Debates about the continued relevance of Marxist theory for twenty-first century capitalism have intensified amid deepening economic inequality, the proliferation of precarious and platform-mediated labor, the ecological emergency, and the fragmentation of collective class identity under digital capitalism. Objective: This study critically examines Marx’s conflict theory of class antagonism and alienation by analyzing how these classical concepts are transformed and intensified in contemporary capitalist production, with particular attention to platform economies, financialization, and the Global South. Methods: A systematic literature review was conducted using Scopus, Web of Science, and Google Scholar, covering peer-reviewed publications from 2019 to 2025 addressing Marxist political economy, class theory, alienation, labor sociology, and digital capitalism. Results: Class antagonism and alienation in contemporary capitalism have undergone structural transformation without losing their essential character: exploitation persists across new labor forms, geographies, and value chains; alienation deepens as digital capitalism colonizes domains previously outside the commodity form. The structural contradictions of capitalism—between labor and capital, production and ecology, global accumulation and local social reproduction—have intensified. Conclusion: Marx’s theoretical legacy remains indispensable for sociological analysis of contemporary capitalism, but requires systematic updating through feminist political economy, eco-Marxism, digital labor theory, and postcolonial critique to capture the full complexity of twenty-first century class relations. Keywords: Marx, class antagonism, alienation, contemporary capitalism, platform economy, precariat, digital labor, eco-Marxism, Global South